Perjanjian Perkawinan Sebagai Alat Perlindungan Hukum: Studi Perbandingan Antara Indonesia, Malaysia, Dan Singapura - Akhmad Kamil Rizani; Ahmad Dakhoir; Aris Sunandar Suradilaga; Muhammad Aulia Rahman (Al-Ahwal Al-Syakhsiyyah: Jurnal Hukum Keluarga dan Peradilan Islam, 2026)
This study aims to analyze and compare the regulation of marital agreements as instruments of legal protection within the family law systems of Indonesia, Malaysia, and Singapore. The study departs from the transformation of the classical Islamic law concept of taklik talak into modern positive legal constructions that accommodate the need to protect the rights and obligations of spouses. This research employs a normative legal method using statutory, conceptual, and comparative approaches. The legal materials consist of statutory regulations, classical and contemporary fiqh doctrines, academic literature, and relevant court decisions. The results of the study show that in Indonesia, the regulation of marriage agreements is contained in Undang-Undang Nomor 16 Tahun 2019, Kompilasi Hukum Islam, and Kitab Undang-Undang Hukum Perdata, characterized by increased flexibility following a Constitutional Court decision allowing agreements to be concluded after the marriage has taken place. In Malaysia, the regulation is more systematically structured under the Akta Undang-Undang Keluarga Islam (Wilayah-Wilayah Persekutuan) 1984, which positions taklik as an integral component of Islamic family law administration. Meanwhile, in Singapore, the regulation falls within the framework of the Administration of Muslim Law Act 1966, which institutionally integrates Sharia principles into the national legal system. Comparatively, the three countries share similarities in recognizing marital agreements as preventive instruments of legal protection, yet they differ in terms of formation procedures, validation mechanisms, and binding force. The study concludes that the effectiveness of marital agreements is significantly influenced by each country’s normative design and institutional legal structure. Therefore, strengthening regulatory frameworks and harmonizing legal protection principles based on justice and legal certainty are urgent necessities for the development of Islamic family law in Southeast Asia.